(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This work aims to create an information system for classifying dialects and identifying dialectics using a neural network model and a logical inference mechanism based on the rules of fuzzy logic. This system has no explicit analogues for the Russian language, which emphasizes the relevance of this work. To solve the problem, the Python programming language was used with libraries for natural language processing, neural network training, Google Bert model usage and base of fuzzy logic rules creation for the Mamdani model. The research work involved an analysis of dialectology field and a search for methods using natural language processing and machine learning methods for dialect tasks. The author offered the architecture of the neural network model for the dialect classification and formed the basic concepts of the dialethism’s determination algorithm. The next step was a neural network model training on Bert outputs and dialethism’s determination experimental algorithm implementation.